Exploring the needs and expectations of international students towards The National University of Malaysia (UKM) - Mohammed Fadel Arandas,; Shahrul Nazmi Sannusi,; Loh, Yoke Ling (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2019)
This study demonstrates main reasons for choosing The National University of Malaysia (UKM) by international students and their needs and expectations toward the University. The study also shows the obstacles faced by those students and their satisfaction towards UKM. A total of 108 questionnaires were distributed in the main campus to the respondents who came from ten diffident countries. The main reasons for choosing UKM were its high ranking, reasonable tuition fees, faculty, programmes, and lecturers respectively. The results revealed that the main obstacles faced international students were tough visa procedures, improper hostels, social isolation and discrimination, and bureaucracy. Both the facilities and services of UKM and the studying approach have met the expectations satisfaction of international students. Yet, both social relationship and participation in activities and living conditions in UKM hostels have disappointed international students and did not meet their satisfaction. This study suggested that UKM should establish counselling unit and organise regular meetings to listen to the problems and suggestions of those students. Volunteer and pre-enrolment activities should be organised to introduce the Malaysian culture and gather international students with their local peer. Moreover, international students should be provided upon their arrival to UKM by hostels that combine proper conditions of living at a reasonable price.